ASSESSMENT OF PATIENTS’ RECORD MANAGEMENT AND EFFICIENT HEALTHCARE SERVICE DELIVERY IN TERTIARY HEALTH INSTITUTIONS IN ABUJA, NIGERIA - Ogbonnaya, Okafor Cyprian (2023)
This master’s thesis comprehensively analyzes patient record management and its impact on healthcare service delivery in three tertiary health institutions in Abuja, Nigeria: University of Abuja Teaching Hospital, National Hospital, and Federal Medical Centre. Employing a mixed- method approach, the research combined both qualitative and quantitative methodologies. Qualitatively, in-depth interviews with a total 21 staff members from the 3 public healthcare institutions were interviewed with the aim to understand the current state of their patient record creation and management processes, identifying the challenges and opportunities to enhance service delivery. A total number of quantitative data, 187 patient respondents and 21 record management staff respondents were analyzed and interpreted using simple percentage and descriptive statistics. The findings reveal that most patients' data about (89.8%) are stored in digital formats, while 10.2% of the total sample population (N=187) record are stored on paper system, the finding indicated inefficiencies and disparities in their record management processes, particularly affecting outpatients, and referral patients. The findings emphasize the need for a more effective digitalization process and suggest improvements in data management practices, aligning with the Nigeria Data Protection Act and international data management standards. This study contributes to understanding record management in Nigerian healthcare institutions and proposes actionable recommendations for enhancing efficiency and consistency in patient care.